Treatment of Severe Recalcitrant Fungal Keratitis Using Subconjunctival Fluconazole as an Adjunctive Therapy: http://doi.org/10.36351/pjo.v37i2.1081 - Gull, Ambreen; Niazi, Fuad Ahmad Khan; Raza, Ali (Pakistan Journal of Ophthalmology, 2021)
Purpose: To evaluate the safety and effectiveness of 2% subconjunctival injection of Fluconazole as an adjunctive treatment in severe recalcitrant fungal keratitis. Study Design: Interventional case series. Place and Duration of Study: Ophthalmology department of Holy family hospital, Rawalpindi medical university, from January 2019 to August 2019. Methods: The study included 18 eyes of 18 patients with severe resistant fungal corneal ulcer.We excluded those cases who had known hypersensitivities to Fluconazole. These ulcers were refractory toprimary conventional antifungal therapy with topical Natamycin, topical and systemic Fluconazole. Sample for culture was taken with sterile cotton bud and scraping was taken with kimura spatula. All resistant cases were given1.0 ml of 2% subconjunctival Fluconazole injection once a day for at least one week. After that depending upon the condition, the injections were givenonalternate days for 2 weeks. Results: Average age of the patients was 35.22 years (SD ± 10.42). Among total 18 patients, six (33.33%) were females and 12 (66.67%) were males. Thirteen (72.22%) cases showed absolute response after one week and 5 (27.77%) cases needed more injections. Four (22.22%) of these 5 cases partiallyimproved andone case failed to show improvement. Final vision varied in different cases according to the position of the residual scar. Five cases ended up in keratoplasty. Local or systemic toxicity was not seen in any case. Conclusion: Subconjunctival injection of 2% Fluconazole can be used as an adjunctive therapy for severe fungal keratitis without any toxic complications. Key Words: Keratomycosis, Evisceration, Keratoplasty.